Active Suppression of Rotating Stall Inception with Distributed Jet Actuation - Huu Duc Vo (International Journal of Rotating Machinery)
An analytical and experimental investigation of the effectiveness of full-span distributed jet actuation for active suppression of long length-scale rotating stall inception is carried out. Detailed modeling and experimental verification highlight the important effects of mass addition, discrete injectors, and feedback dynamics, which may be overlooked in preliminary theoretical studies of active control with jet injection. A model of the compression system incorporating nonideal injection and feedback dynamics is verified with forced response measurements to predict the right trends in the movement of the critical pole associated with the stall precursor. Active control experiments with proportional feedback control show that the predicted stall precursors are suppressed to give a 5.5% range extension in compressor flow coefficient. In addition, results suggest that the proposed model could be used to design a more sophisticated controller to further improve performance while reducing actuator bandwidth requirements.